Pamali in the Perspective of Local Wisdom: A Dilemma in Tourism Development in the Coastal Areas of Tanimbar Islands Regency - Risakotta, Tesalonika Kezia; Solissa, Hermelina (Agrikan Jurnal Agribisnis Perikanan, 2024)
This study investigates the impact of pamali, an unwritten cultural rule in the local tradition of the Tanimbar Islands Regency, on tourism development. The aim of this research is to understand how these cultural rules shape the views and behavior of local residents and how the community influences tourism in the Tanimbar Islands. The study employs a mixed-methods design, utilizing various methods to collect data from four primary tourist villages. The findings are expected to provide insights into how pamali affects tourism and to offer strategies for sustainable tourism development without violating culturally sensitive rules. This research brings a new perspective by focusing on the Tanimbar Islands Regency and its efforts to harmonize tourism and local culture. The results indicate that pamali plays a significant role in the lives of the people of the Tanimbar Islands (KKT), with a strong understanding of its values. There is a positive correlation between the understanding of pamali and community attitudes towards tourism, with a coefficient of determination of 78.7% and a regression coefficient of 0.880 (p < 0.001), signifying a strong influence on community participation. Tourism promotion strategies that emphasize pamali education have proven to be effective (t = 30.220, p < 0.001) in enhancing visitor experiences and avoiding cultural conflicts. Recommendations include increasing education efforts, involving local communities in planning, and developing tourism products based on local wisdom to ensure sustainable tourism.